Collaborative Potential of Virtual Communities: Case Study of "Connect" - Božić, Jasmina; Bakić-Tomić, Ljubica; Srbljinović, Armano (2007)
The study explores the potential of information technologies, and particularly those of virtual communities, to act as vehicles that enhance human cooperation. The endeavour to improve positive and to suppress negative incentives for cooperation among members of virtual communities calls for framework principles which would facilitate design of viable cooperative on-line communities. In this study Elinor Ostrom's design principles of robust, long enduring, common-pool resource institutions are used as evaluation matrix in the assessment of cooperation potential of "Connect", the virtual community of Croatian scientists. The case study of compliance of "Connect" to Ostrom's principles is undertaken in search of positive and negative instances of cooperation among "Connect" members, with a view to explain certain cases of successful cooperation, as well as cooperation breakdown within the "Connect" community. The purpose of the study is to investigate the ability of Ostrom's principles to indicate design features of virtual communities which are relevant for the development of genuinely cooperative communities.
Projekt MZOS
ENG